2018
DOI: 10.1016/j.enbuild.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Interior insulation—Characterisation of the historic, solid masonry building segment and analysis of the heat saving potential by 1d, 2d, and 3d simulation

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…1 Average of two pH tests. 2 Samples from the outermost 10 mm of the insulation, near the interface between masonry and insulation.…”
Section: Ph and Mould Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Average of two pH tests. 2 Samples from the outermost 10 mm of the insulation, near the interface between masonry and insulation.…”
Section: Ph and Mould Growthmentioning
confidence: 99%
“…A high energy saving potential is found in retrofitting of historic masonry external walls [1]. Solid masonry buildings from 1850-1930 account for 41% of all Danish multi-story residential buildings (3-6+ floors) [2]. Studies have shown average-weighted U-values of 0.83 and 1.12 W/m2•K for external walls in multi-story residential buildings built prior to 1850 and the period 1850-1930, respectively [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk was determined using the mathematical model for wood decay by Viitanen et al [18]. The decay model consists of two processes: (1) Activation process , is the state of the decay and determines the initiation of the Mass Loss (ML) process; (2) ML process, in which irrecoverable ML occurs when = 1. Increase in the activation process and ML occurs when RH ≥ 95% and T > 0 • C. The presented decay modeling was performed using = 1 as initial state.…”
Section: Wood Decaymentioning
confidence: 99%
“…With an increasing desire toward reduction of the global energy demand and the carbon footprint, an increased focus has been put on the building sector. Granted that the existing building stock consists of a large share of buildings constructed prior to 1945, yielding a great potential toward reaching these goals as documented in the segment study by Odgaard et al [1], many of which were built with solid masonry exterior walls. A large portion of these buildings are considered as worthy of preservation, posing several challenges with respect to renovation of the exterior walls as major exterior alterations often are prohibited.…”
Section: Introductionmentioning
confidence: 99%